Risk factors for early hyperbilirubinemia in neonates: A cross-sectional study - T Rehna; Suni Ann Thomas (Journal of Current Research in Scientific Medicine, 2022)
Background: Neonatal hyperbilirubinemia is a commonly encountered problem in the early neonatal period. Hence, this study was undertaken in babies with significant hyperbilirubinemia to find out the factors which had caused an early rise of bilirubin (≤48 h) in some neonates compared to those who develop hyperbilirubinemia by 72 h. Factors that can predict early hyperbilirubinemia will help in early intervention. Methodology: This cross-sectional study was conducted in the neonatal intensive care unit of a tertiary care center from March 2021 to January 2022 among 405 healthy term neonates with significant hyperbilirubinemia. Serum bilirubin values were routinely done at 72 h, and earlier at 48 h if clinical icterus was noted by Kramer's rule and divided into two groups – one with hyperbilirubinemia at 48 h and another with hyperbilirubinemia by 72 h. Statistical analysis was done to find out the factors which could predict early hyperbilirubinemia. Results: Of the 405 neonates with significant hyperbilirubinemia, 270 (66.6%) had early hyperbilirubinemia and 135 (33.3%) had hyperbilirubinemia by 72 h. There were no statistically significant differences between the two groups with respect to sex, birth weight, mode of delivery, and baby blood group. Forty-two (49.4%) neonates with umbilical cord bilirubin (UCB) <2 mg/dl, 113 (65.6%) with UCB 2–2.5 mg/dl, 75 (72.1%) with UCB 2.5–3 mg/dl, 34 (89.5%) with UCB 3–3.5 mg/dl, and 6 (100%) with UCB >3.5 mg/dl developed early hyperbilirubinemia. Sixty-four (79%) neonates with bilirubin–albumin ratio (BAR) ≥0.79 developed early hyperbilirubinemia compared to 206 (63.6%) neonates with BAR <0.79 who had early hyperbilirubinemia. Conclusions: The UCB and bilirubin–albumin ratio correlated well with the development of early hyperbilirubinemia. Hence, it was concluded that those babies with a high UCB >2.1 mg/dl and/or high BAR ≥0.79 should be screened early for the development of hyperbilirubinemia.